Decreasing the carbon footprint of an intensive rice-based cropping system using conservation agriculture on the Eastern Gangetic Plains - Alam, K.; Bell, R.; Biswas, Wahidul (Elsevier, 2019)
Emerging conservation agriculture (CA) technologies are being applied in rice-upland cropping systems and their potential to mitigate greenhouse gas emissions of the whole rice-based cropping systems could be significant in South Asia especially if they increase soil organic carbon (SOC) stocks. A streamlined life cycle assessment was conducted in the Eastern Gangetic Plains (Bangladesh) to determine greenhouse gas emissions from successive crops of monsoon rice (Oryza sativa), mustard (Brassica juncea) and irrigated rice under CA practices in contrast with the conventional crop establishment practice while accounting for changes in SOC. The life cycle greenhouse gas tonne−1 rice equivalent yield was assessed for four cropping practices: a) traditional crop establishment practices with farmers’ practice of minimal residue return, or b) CT with return of increased residues; c) strip planting (for mustard)/transplanting on non-puddled soils (for rice) with farmers’ practice of minimal residue return or; d) strip planting/non-puddled transplanting with increased residue return. The global warming potential values for the 100-year timescale were used to calculate CO2eq emissions within the system boundary. The net life cycle greenhouse gas emissions after allowing for changes in SOC sequestration varied from 0.73 to 1.12 tonne CO2eq tonne−1 rice equivalent yield. In the annual cropping system, methane (CH4) released from on-farm stage of the life cycle assessment, particularly from the rice crops, represented the dominant contributor to life cycle greenhouse gas emissions. The greenhouse gas emitted by machinery usage during the on-farm stage (irrigated rice), CO2 emission from soil respiration (monsoon rice), and greenhouse gas related to manufacture of inputs (mustard) were secondary sources of emission, in that order of priority. The non-puddlled transplanting of soil with low and increased residue retention were the most effective greenhouse gas mitigation options when sequestered SOC was taken into account (they avoided 35% of the net life cycle footprints compared with current farmers’ practice) in footprints of component crops of the rice-upland cropping system. The CA approaches being developed for the Eastern Gangetic Plains involving strip planting or non-puddled transplanting of rice have potential to mitigate global warming potential of intensive rice-based triple cropping systems but the life cycle assessment approach needs to be applied to a more diverse range of rice-based cropping systems.